Hi! I'm new here and I'm not sure this is the right sub-forum...
But anyway, I'm learning about quaternions, and reading the book John Vince - Quaternions for Computer Graphics. And he is proving that the quaternion notation q = [s, v], have the same "algebraic" rules as the other ways of representing quaternions.
And now he is proving that i*j = k, j*k = i, k*i = j, in that notation, so here is how it goes:
ij = [0, i][0, j]
= [-i * j, i×j]
I get that i×j = k, but -i*j = 0?
How does that work? I have searched for this and it's not mentioned anywhere?
Thanks in advance!